Pengaruh Persepsi Harga, Promosi dan Kualitas Layanan terhadap Loyalitas Pelanggan di Perusahaan Forwarder PT. Citra Selaras Logistik - Yeni Supriatna; Hendratmoko Hendratmoko (Syntax Corporation Indonesia, 2024)
The purpose of this study is to analyze the effect of price, promotion and service quality on customer loyalty mediated by several customers of PT. Citra Selaras Logistik (PT. CSL). This study was conducted using a saturated sampling technique and applied in SmartPLS 4.0. This research shows that price perception has negative influence and is not significant to customer loyalty, while promotion and quality service have positive influence and are significant to customer loyalty.